The serpent kills or the serpent gives life : the kabbalist Abraham Abulafia's response to Christianity - Sagerman, Robert (Supplements to The journal of Jewish thought and philosophy ;, 2011)
Abraham Abulafia (1240 - c. 1291) founded an enormously influential branch of Jewish mysticism, referred to as the prophetic or ecstatic kabbalah. This book, from several perspectives, explores the impact of Christianity upon Abulafia. His copious writings evince an intense fascination with Christian themes, yet Abulafia's frequent diatribes against Jesus and Christianity reveal him to be deeply conflicted in his relationship to his southern European religious neighbors. This book undertakes a careful study of Abulafia's writings, suggesting that the recognition of an inner dynamic of attracti.